METHOD FOR FORMING OF MULTISERVICE CORE MOBILE COMMUNICATION NETWORK SLICES - Sulima, S. V. (Radio Electronics, Computer Science, Control, 2019)
Context. With the growth in the volume of mobile data traffic and the number of services provided by the mobile network, service load flows are also increasing, which necessitates changing the principles, models and methods of telecommunication flows serving in order to ensure the given quality of providing a wide range of services in flexible and cost-effective way. Advantages of scalability and elasticity with the support of a high rate of network technical resources utilization can be achieved using virtualization technologies and the concept of network slicing, that allows deploying dedicated virtual networks based on services, using the methods of network functions virtualization. In this context, the main question remains what number of network slices will be feasible in terms of the cost of slice managing and providing the required functionality. Objective. To improve the efficiency of mobile network through optimal slice forming in multiservice telecommunication network. Method. Analysis of the publications devoted to network functions virtualization has shown the organization approach of using the multiservice mobile network resources, and also showed insufficient efficiency of existing solutions on important issues of this process (the performance of the slices formation algorithm, the level of functional costs). Results. A method to model network resource allocation system, which forms dedicated network slices that serve certain types of services independently on the common infrastructure. Conclusions. The article solves the problem of constructing a method for forming multiservice core mobile communication network slices, which, due to the effective dynamic configuration of the system, allows providing a wide range of services with a given quality indicators. A model of resource management system is constructed, which is used to present a method that takes into account costs associated with excessive resource allocation, and also reduces the number of network configuration recalculations, which allows achieving a rational ratio of management costs and Quality of Service